Effect of Cooling Rate in the Vicinity of Eutectic Temperature Characteristic for Cryoprotectant Aqueous Solution on Post-Thaw Viability of Saccharomyces cerevisiae and Escherichia coli Cells - Gurina, Tatyana M.; Vysekantsev, Igor P.; Polyakova, Anna L. (Problems of Cryobiology and Cryomedicine, 2013)
The effect of various cooling rates in the range of eutectic temperatures of aqueous solutions of cryoprotectants (dimethyl sulfoxide, glycerol, polyethylene oxide with molecular mass 1500, 1,2-propane diol) on viability in cell suspesion of Saccharomyces cerevisiae and Escherichia coli was studied. The cell suspensions were cooled in these temperature ranges with controlled (1 and 25 deg/min) and non-controlled (plunging into liquid nitrogen) rates. Application of controlled cooling rates in eutectic temperature range of the studied cryoprotectant solutions was shown to be prospective for increase the post-thaw viability of microorganisms. The highest indices of viability of S. cerevisiae and E. coli were obtained for the cooling rate of 25 deg/min. This tendency was kept for all the studied concentrations of cryoprotective agents (5, 10, 15, 20%). The findings are recommended to be considered when developing the freezing protocols for other biological specimens.Probl Cryobiol Cryomed 2013; 23(1):15-25.